IN VITRO SHOOT PROLIFERATION OF BEGONIA PAVONINA: A COMPARISON OF SEMISOLID, LIQUID AND TEMPORARY IMMERSION MEDIUM SYSTEM - Rosilah Ab Aziz; Kodi Isparan Kandasamy; Faridah Qamaruz Zaman; Parameswari Namasivayam (Journal of Academia, 2021)
The in vitro shoot proliferation of endemic Begonia pavonina in three culture conditions i.e semisolid medium (SM), liquid culture medium (LM) and in temporary immersion medium; RITA System (TIM) was analyzed in this study. To minimize contamination rates, seeds were surface sterilized and cultured on MS basal media. The clean raised shoots were then used as explants for inoculation onto the tested culture conditions. For this experiment, the explants were maintained in MS medium supplemented with 0.1mgL-1 BAP for shoot multiplication. After 4 weeks of incubation, higher regeneration rates were observed in TIM as compared to other medium conditions. The propagation rate in TIM was nearly doubled as compared to liquid as well as in solid medium. Shoot hyperhydration was also lowest in a TIM system. Overall, TIM has shown to produced higher shoot multiplications combined with healthy morphological characteristics of plantlets. Shoot cultures from the all cultures successfully rooted in vitro and acclimatized well in the greenhouse.